Soziologien des Lebens Überschreitung - Differenzierung - Kritik - Delitz, Heike; Nungesser, Frithjof; Seyfert, Robert (Sozialtheorie, 2018)
The various sociologies of life do not interpret life only as the object that is socially standardized, enhanced and recognized. They always see it as a subject of its norms, its knowledge and its changes as well. Life is not one-sided; instead its entanglements are analyzed: the immanence of nature and culture; the concurrence of being active and passive; the co-constitution of affect and cognition; the identity of normativity and standardization. Following authors such as Bataille, Bergson, Canguilhem, Deleuze, Driesch, Plessner, the pragmatists or Simmel, the contributions featured in this book unfold different perspectives on the sociology of life, re-vitalizing a discourse that is instructive for sociological theory in a variety of ways.